Microencapsulation of limonene for textile application - Rodrigues, S.N. (2010)
Polyurethane−urea microcapsules with limonene oil as the active agent were produced by interfacial polymerization, and their suitability for textile applications was studied. Experimental conditions for the textile substrates impregnation were based on industrial requirements and set up at laboratory scale using a mini-foulard. The success of the polymerization reaction leading to the formation of the polyurethane−urea shell was checked by Fourier transform infrared spectroscopy. Particle size distributions and morphology of the microcapsules were studied using a particle size analyzer (Coulter LS230), optical microscopy, and scanning electron microscopy. The effectiveness of the textiles impregnation and the durability of the impregnation effect were evaluated by scanning electron microscopy and by headspace/GC/FID. Under the present research, a product was developed and its performance, in regard to industrial requirements, was successfully tested.